Can Shareholder Litigation Discipline CEO Bonuses in the Financial Sector? The Role of Securities Class Actions. (24th October 2015) - Dalla Pellegrina, Lucia; Saraceno, Margherita
Abstract : There is evidence that, especially in the financial sector, CEOs are rewarded with very high bonuses. This phenomenon vividly contrasts with the alleged executive misbehaviour which fueled securities litigation during the recent financial turmoil. This paper empirically investigates the relationship between securities class actions (SCAs) and the growth of CEO bonuses in the period 1999–2010 for financial intermediaries included in the S&P500 index. An instrumental variable related to US Federal Courts' Guidelines is exploited to address endogeneity issues. The analysis shows that SCAs are likely to moderate the dynamics of bonuses. This result supports the idea that private enforcement provided by securities litigation works as a complementarity tool of corporate governance aimed at 'shielding' small shareholders and other investors against inefficient risk undertaking which is in turn reflected in sizeable executive bonuses.